Evaluation of Some Rapeseed Mutants Based on Morpho-Physiological, Biochemical and Yield Attributes (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted at the field laboratory of Bangladesh Institute of Nuclear Agriculture, Mymensingh, to investigate morpho-physiological characters, yield attributes and seed yield in seven advanced mustard mutants viz., RM 01,RM 02,RM 03,RM 04,RM 05,RM 10 and RM11along with a cultivar BINAsarisa-4.The experiment was laid out in a Randomized Complete Block Design with three replications. High yielding genotypes showed superiority in leaf chlorophyll content, photosynthesis, total sugar content and nitrate reductase activity. RM 05 produced higher number of siliqua plant-¹ resulting higher seed yield. In contrast, the mutants RM 01 and RM 10 produced the lower number of siliqua plant-¹ and also showed the lower seed yield with being the lowest in RM01.Among the mutants/cultivars, RM 05 produced the highest seed yield due to morpho-physiological superiority than the others.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14831 J. Environ. Sci. & Natural Resources, 5(2): 281-285 2012